9 Historian – multilingual, internet, psychiatric history taking with english output and mobile tablet history taking with automated analysis and diagnosis. (31st October 2017) - Taylor, Jason
Abstract : Project Aims: To enable rapid and detailed assessment of new psychiatric referrals. To enable better prioritisation of service access for such referrals. To enable patients to engage actively in the history taking process and have histories taken at home should they so wish. To enable histories to be taken in a range of languages with an instant English output. Historian was developed by the author and is freely accessible at www.historian.uk.com. The program employs a "pick and click" statement-based approach to history taking whereby the patient "mouse-clicks" relevant items. Historian intelligently formats the responses and builds up an anonymised, comprehensive history and self-report mental state for printing out or emailing. Historian offers instant English output from over 15 languages. Method: The study sample comprised 27 new case outpatient referrals to adult psychiatry. A letter and information sheet, outlining the nature of the study and a request for consent to participate, was sent with the initial appointment letter for each appropriate referral. Patients who could be identified from the referral letter as having organic problems were excluded. Consenting patients were randomly allocated so that half would receive the face-to face (clinician's) interview first, followed by the computer interview; the other half of the sample would conduct the computer interview, followed by the clinician's interview. In view of the potential fluctuation of symptoms, the computerised and clinician interviews were arranged within a two-week time frame of each other. Results: The 'Historian' interview elicited a significantly more comprehensive psychiatric history in 20 out of 35 categories. Analyses showed that the mean items mentioned in the computer interview (mean=22.8, sd=4.83) was greater than in the clinician's interview (mean=15.5, sd=7.61). Paired samples t test analyses showed that the difference between items in the two types of interviews result was highly significant (t=4.359, p<001). Separate paired t test analyses of patients receiving the computer interview before the clinician interview (t=20.5, p<0.01); and patients having the clinician interview before the computer interview (t=19.6, p<0.01) revealed similar results. The system was found to be highly acceptable to patients on a range of measures. Historian Mobile Platforms: Comprehensive English psychiatric history and self-report mental state software has been developed by the author for the use on mobile tablets. (iOS and Android devices). The free apps do not incorporate any translation capability but offer an automated assessment of the completed history, highlighting key features and risks and offering psychiatric diagnoses based on the selections made. The diagnostic component of the system has yet to be evaluated. This project had no external financial support and is non-commercial.